2019
DOI: 10.3390/su11030766
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Educational Investment on Sustainable Economic Growth in Guangdong, China: A Cointegration and Causality Analysis

Abstract: Education, as an investment in human capital, is regarded as an important determinant of sustainable economic growth [1,2]. The purpose of this study is to explore the cointegration and causality between the investment in education and sustainable economic growth in Guangdong province by using the panel data of 21 cities from 2000 to 2016. We construct a variable intercept panel data model with an individual fixed effect based on the Cobb-Douglas production function, estimating the contribution of the investme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 32 publications
3
28
1
3
Order By: Relevance
“…In addition, many studies have also focused on the role of investment in education and the educational quality. For example, Keller [8] and more recently Liao, Du, Wang, and Yu [13] have considered the role of educational investment in economic growth. They examined this hypothesis in Guangdong, China and found that personal financial investment in education has a positive role in enhancing economic growth, but the magnitude of the impact can vary in different areas.…”
Section: Literature Review 21 Human Capital Education and Higher mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, many studies have also focused on the role of investment in education and the educational quality. For example, Keller [8] and more recently Liao, Du, Wang, and Yu [13] have considered the role of educational investment in economic growth. They examined this hypothesis in Guangdong, China and found that personal financial investment in education has a positive role in enhancing economic growth, but the magnitude of the impact can vary in different areas.…”
Section: Literature Review 21 Human Capital Education and Higher mentioning
confidence: 99%
“…In the recent decade, the existing literature has broadly discussed the relationship between education and economic growth. Many investigations have revealed that education has a potential effect on economic growth (see, e.g., [10][11][12][13]). Existing studies mainly use linear models of education's impacts on economic growth, which may be a good approximation and conform with many theoretical approaches.…”
Section: Education and Economic Growth: Modeling Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Two third of Gross Domestic Product (GDP) growth is explained by cognitive skills of the population (Hanushek, Weissman, Jamison, & Jamison, 2008). The empirical evidences of positive contribution of education on the economy were also supported by McMahon (1998), Asteriou and Agiomirgianakis (2001), Petrakis and Stamatakis (2002), Self and Grabowski (2003;, Lin (2003;, Dickens, Sawmill and Tebbs (2006), The International Institute for Applied Systems Analysis (IIASA) (2008), Aghion, Boustan, Hoxby, and Vandenbussche (2009), Barro (2013), Pegkas (2014), and Liao, Du, Wang, and Yu (2019) among others. Education is also an essential mechanism to eradicate poverty as the probability of escaping poverty is associated with an increase in education (Patel, 2014).…”
Section: Introductionmentioning
confidence: 87%
“…Lin [14] studied the case of Taiwan and shows that education had a significantly positive impact on economic growth over the period of 1965-2000. Using panel data from 2000 to 2016 on Guangdong Province in China, Liao et al [15] demonstrated that local financial investment in education results in a statistically significant positive impact on sustainable economic growth. Diebolt and Hippe [16] focused on the long-run consequence of human capital on economic development and demonstrate how the past regional human capital contributes to rationalizing the current disparities in economic development in Europe.…”
Section: Literature Reviewmentioning
confidence: 99%